2010
DOI: 10.1359/jbmr.090832
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-dependent inhibition of mineralization by osteopontin ASARM peptides is regulated by PHEX cleavage

Abstract: The SIBLING family (small integrin-binding ligand N-linked glycoproteins) of mineral-regulating proteins, which includes matrix extracellular phosphoglycoprotein (MEPE) and osteopontin (OPN), contains an acidic serine-and aspartate-rich motif (ASARM). Xlinked hypophosphatemia caused by inactivating mutations of the PHEX gene results in elevated mineralization-inhibiting MEPE-derived ASARM peptides. Although the OPN ASARM motif shares 60% homology with MEPE ASARM, it is still unknown whether OPN ASARM similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
194
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(211 citation statements)
references
References 52 publications
11
194
1
1
Order By: Relevance
“…(13) These findings align with the concept that proteolytic processing of OPN and its peptides by PHEX contribute to the local control of crystal growth in bone mineralization. The selectivity of PHEX hydrolysis for OPN degradation relative to other acidic SIBLING proteins was assessed using another phosphorylated protein-BSP-also thought to play a role in bone and tooth mineralization and which in vitro acts as a potent nucleator of mineralization.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…(13) These findings align with the concept that proteolytic processing of OPN and its peptides by PHEX contribute to the local control of crystal growth in bone mineralization. The selectivity of PHEX hydrolysis for OPN degradation relative to other acidic SIBLING proteins was assessed using another phosphorylated protein-BSP-also thought to play a role in bone and tooth mineralization and which in vitro acts as a potent nucleator of mineralization.…”
Section: Discussionsupporting
confidence: 77%
“…Phosphorylated full-length OPN is a potent mineralization inhibitor of osteoblast cell cultures, (19) as are its phosphorylated peptides, (13,15) with some evidence for an inhibitory function in bone in vivo. (34) Thus, both the full-length protein and its peptides appear to be important in the inhibition of mineralization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different aspects of collagen phosphorylation on processing, fibril formation or protein interactions have recently been reviewed (46). Other noncollagenous extracellular matrix proteins are also crucial in bone and tooth formation via the control of hydroxyapatite crystallization (47,48). These secretory calcium-binding phosphoproteins (osteopontin, OPN; dentin matrix protein-1, DMP1; bone sialoprotein, BSP; matrix extracellular phosphoglycoprotein, MEPE and dentin sialophosphoprotein, DSPP) belong to the small integrin-binding ligand N-linked glycoprotein (SIBLING) family and are heavily phosphorylated (49).…”
mentioning
confidence: 99%
“…It was recently demonstrated that osteopontin (OPN), a member of the small integrin-binding ligand N-linked glycoproteins family, is also a source of ASARM peptide. Phosphorylated ASARM peptide derived from OPN was able to inhibit mineralization in osteoblast cultures and the addition of PHEX rescues this effect (Addison et al 2010). Consequently, a possible dual mechanism for PHEX has been suggested: to prevent the release of ASARM peptides from proteins like MEPE and OPN and to promote ASARM's degradation.…”
mentioning
confidence: 99%